2020
DOI: 10.2147/opth.s238756
|View full text |Cite
|
Sign up to set email alerts
|

<p>Dexamethasone 0.4mg Sustained-Release Intracanalicular Insert in the Management of Ocular Inflammation and Pain Following Ophthalmic Surgery: Design, Development and Place in Therapy</p>

Abstract: Inflammation and pain are two prevalent findings after ocular surgery. Corticosteroids are widely administrated as a core treatment to control post-surgical inflammation and pain. Improper patient adherence to post-operative eye drop regimens, limited bioavailability of topical eye drops, and the negative impact of preservatives used in many of these eye drops, has made a strong case for novel therapies in the treatment of post-operative pain and inflammation. This review of the literature will focus on the ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 35 publications
1
12
0
Order By: Relevance
“…Such examples have been reported in literature using poly(ethylene glycol) (PEG) with zinc ion bridging [ 118 ] for DexSP nanoencapsulation and PLGA microspheres [ 119 , 120 ] where DexSP was released up to 25 and 30 days, respectively. Similar extended release profiles of Dex have been reported for intracanalicular applications (up to 30 days) [ 121 ] and up to 12 days from poly(ɛ-caprolactone) nanofibers [ 122 ]. However, these polymers have low mucoadhesion and thus cannot be used in drop eyes solutions.…”
Section: Resultssupporting
confidence: 75%
“…Such examples have been reported in literature using poly(ethylene glycol) (PEG) with zinc ion bridging [ 118 ] for DexSP nanoencapsulation and PLGA microspheres [ 119 , 120 ] where DexSP was released up to 25 and 30 days, respectively. Similar extended release profiles of Dex have been reported for intracanalicular applications (up to 30 days) [ 121 ] and up to 12 days from poly(ɛ-caprolactone) nanofibers [ 122 ]. However, these polymers have low mucoadhesion and thus cannot be used in drop eyes solutions.…”
Section: Resultssupporting
confidence: 75%
“… 33 Two prospective multicenter studies observed a reduction in ocular pain and inflammation compared to a placebo device. 38 Ninety-six percent of patients were satisfied with the use of Dextenza and 88% would want to use the insert again after ocular surgery. 39 These results demonstrate that there is market potential for noninvasive drug delivery devices.…”
Section: Discussionmentioning
confidence: 96%
“…Nevertheless, the animals in this study showed some signs of inflammation after implantation, and antiinflammatory eye drops were necessary to prevent rapid implant degradation [17]. Therapeutic regimens for topically applied corticosteroids are rigid and often comprise frequent drug administration [18,19]. This might cause limited compliance and could be a challenge for clinical feasibility since patient adherence to the therapy is essential to avoid rapid degradation of the transplanted material [17].…”
Section: Introductionmentioning
confidence: 99%